Quality of Financial Reporting and Organizational Performance. A Case Study of Airtel Uganda - Bua Jerum Enyang (Uganda Christian University, 2025)
This research investigated the quality of financial reporting and its impact on organizational performance at Airtel Uganda. The objectives were to analyze the impact of quality financial reporting on organizational performance, Identify the key factors affecting quality financial reporting and to examine the challenges faced in enhancing quality financial reporting. It examined how accurate financial reporting influenced decision-making, stakeholder confidence, and overall business success. The total population size was 100 employees; the recommended sample size was 80 employees. Data was collected through interviews and questionnaires involving respondents from various levels within the organization. The study Findings revealed that high-quality financial reporting significantly enhances organizational performance by improving decision-making processes and fostering stakeholder trust. Key factors affecting reporting quality include adequate training, modern accounting technology, and effective internal controls. However, the research revealed Challenges such as a lack of skilled personnel and poor inter-departmental communication which were identified as barriers to achieving optimal reporting standards. The study concludes that investing in training, embracing technology, and enhancing communication are essential for improving financial reporting quality and, consequently, organizational performance. The study Recommends for ongoing evaluation and adaptation of financial practices are also provided to ensure long-term success, the adoption of advanced technological solutions, strengthen internal controls and improve communication with in the organization
Undergraduate